An Attempt at a New Systematization of the Studying Course of the Special Administrative Law - Nikolova, Raina (Yearbook of the Law Department, 2019)
The article analyzes in historical context the systematization of the academic discipline, studying the administrative material law – special part. The author makes a new systematization of the course Special Administrative Law by using the three stateforming elements – population, territory, state power – as a distinguishing criterion. This new systematization if as follows: the Administrative law of citizens, the Administrative Territorial law, the Administrative Business law, the Administrative Non-profit law.